SIMULATION CONTROL SYSTEM DESIGN WITH SCILAB AND XCOS: SIMULATION CONTROL SYSTEM DESIGN WITH SCILAB AND XCOS - Ikhsan Parinduri; Melda Panjaitan (INFOKUM, 2021)
The control system is designed to facilitate the performance of an electronics design. Design on Sclib for work simulation in the form of block diagrams with Xcos features. The input must match the connected component variables based on the mathematical formula. The design stages in this research are P, I, D control and DC motor. Modeling on analog, physical and system design modeling with simulation outputs on control system design block diagrams. The application of Sclib to Xcos features helps in learning electronics, electrical and simulation system design.